STUDY OF BASELINE WIDAL TITRE AMONGST APPARENTLY HEALTHY INDIVIDUALS IN AND AROUND MUZAFFARNAGAR CITY OF UTTARPRADESH, INDIA - DR. SAPNA CHAUHAN; MR. SACHIN SHARMA (International Journal of Pharma and Bio Sciences, 2016)
Typhoid fever remains a very important public health problem in developing countries like India. It is endemic in almost all parts of India. Widal test is widely used for its diagnosis; however there are several limitations to the test. The interpretation of the single Widal test depends upon the baseline titre prevalent amongst healthy individuals in a particular geographical area. Hence the study was undertaken to determine the baseline Widal titre from the apparently healthy population in and around Muzaffarnagar city of Uttarpradesh, India. Blood samples were collected from healthy volunteers over the period March 2015 to May 2015.All of these were analyzed for the presence of Salmonella antibodies by carrying out Widal tube agglutination test. Among 250 serum specimens which were tested 142(56.8%) sera were found to be positive for the Widal test and 108(43.2%) were negative. The most frequently recorded titre of the reactive sera was 1:80 for the anti-O antibodies and it was 1:80 for the anti-H antibodies against Salmonella typhi while 1:20 for Salmonella paratyphi A & B. This is baseline titre for this region. Our results suggest that 80 for anti-O antibodies, 80 for anti-H antibodies, 20 for anti-AH and anti-BH antibodies may be considered as diagnostic for Typhoid fever in this region.